2002
DOI: 10.1002/pits.10038
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and child variables as predictors of academic engagement among low‐income African American children

Abstract: A causal model for understanding the complex interplay between student-reported teacher behaviors, student self-systems, and student engagement was tested. One hundred seventeen African American students in grades 1 through 12 completed a comprehensive questionnaire regarding teacher context, self, and engagement variables. A series of hierarchical regression analyses were conducted to test the hypothesized mediation models and to construct a path model. Most hypotheses were supported. Student self-system vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 14 publications
(25 reference statements)
2
123
1
5
Order By: Relevance
“…Há que se notar que a qualidade das relações na escola é perpassada pelo desempenho, e pelo grau de consciência que o aluno tem desse importante aspecto de sua vida escolar. De acordo com Tucker, Zayco e Herman (2002) e Chen (2005, o desempenho é condição sine qua non à adaptação escolar (cumpre a finalidade última da escolarização). Se as aquisições acontecem, como no caso de Gabriel (G), a ligação com a escola e com a própria escolarização parece mais forte e ultrapassa o plano dos relacionamentos pessoais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Há que se notar que a qualidade das relações na escola é perpassada pelo desempenho, e pelo grau de consciência que o aluno tem desse importante aspecto de sua vida escolar. De acordo com Tucker, Zayco e Herman (2002) e Chen (2005, o desempenho é condição sine qua non à adaptação escolar (cumpre a finalidade última da escolarização). Se as aquisições acontecem, como no caso de Gabriel (G), a ligação com a escola e com a própria escolarização parece mais forte e ultrapassa o plano dos relacionamentos pessoais.…”
Section: Discussionunclassified
“…Assim, se a experiência escolar é positiva, é nesse ambiente que os adolescentes investem boa parte de seu tempo diário, participando de atividades educacionais que favorecem o desenvolvimento cognitivo, emocional e social (MASCHIA et al, 2008). Uma boa vinculação à escola desponta como um dos fatores protetivos mais robustos ao engajamento sério de jovens com a prática de delitos (LEBLANC, 1994;LILJEBERG et al, 2011;VAN DER LAAN;BLOM;KLEEMANS, 2009).…”
Section: Introductionunclassified
“…Student engagement included on task behavior defined as reading, writing, responding to questions, reacting to prompts and task completion. Recommended rates of student engagement (active, passive or combined) are not available; however, a general understanding that student engagement level is a strong predictor of student achievement is evident in the research (Greenwood et aL, 2002;Tucker et aL, 2002). Previous research found general levels of student engagement for students exhibiting behavior concems between 49% and 94% in an instructional context (Baker et aL, 2008;Hayling et aL, 2008).…”
Section: Findings and Relation To Previous Researchmentioning
confidence: 99%
“…Student engagement variables of disability status, social economic status and race/ethnicity further describe the differences in student engagement (Baker et aL, 2008;Tucker et aL, 2002). In addition, engagement is associated with positive student outcomes across learning environments.…”
Section: Teaching For Student Engagementmentioning
confidence: 99%
See 1 more Smart Citation